Flow cytometric analysis of cerebrospinal fluid identifies patients with occult central nervous system involvement in relapsed pediatric acute lymphoblastic leukemia - Maria Thastrup; Hanne Vibeke Marquart; Mette Levinsen; Aina Ulvmoen; Birgitte Klug Albertsen; Cornelis Jan Pronk; Marianne Olsen; Peder Wehner; Mervi Taskinen; Bodil Als-Nielsen; Kjeld Schmiegelow (Haematologica)
Not available.